2012
DOI: 10.1128/aac.06191-11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of qnr , aac(6)-Ib-cr , qepA , and oqxAB in Escherichia coli Isolates from Humans, Animals, and the Environment

Abstract: qnr, aac(6=)-Ib-cr, qepA, and oqxAB genes were detected in 5.7%, 4.9%, 2.6%, and 20.2% of 1,022 Escherichia coli isolates from humans, animals, and the environment, respectively, collected between 1993 and 2010 in China. The prevalence of oqxAB in porcine isolates (51.0%) was significantly higher than that in other isolates. This is the first report of oqxAB-positive isolates from ducks and geese and as early as 1994 from chickens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(89 citation statements)
references
References 16 publications
6
78
3
2
Order By: Relevance
“…The widespread use of these compounds may exert selection pressure for the rapid emergence of oqxAB in swine and poultry isolates. These chemical compounds are seldom used in cattle (13). Humans may be exposed to these resistant bacteria through visits to farms, wet markets, and contacts with contaminated meats (17,38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The widespread use of these compounds may exert selection pressure for the rapid emergence of oqxAB in swine and poultry isolates. These chemical compounds are seldom used in cattle (13). Humans may be exposed to these resistant bacteria through visits to farms, wet markets, and contacts with contaminated meats (17,38).…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported primers were used to detect oqxA and oqxB (13). PCR mapping was used to detect the presence of IS26 elements on the two sides of oqxAB (see Table S2 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Since then PMQR genes have been described in several bacterial isolates particularly members of the Enterobacteriaceae family worldwide. 13,15,20,21,22 The qnr genes are known to produce proteins (QNR proteins) that protect the quinolone targets from inhibition. Studies have shown that they produce a low level resistance, but facilitate a higher level resistance in association with chromosomal mutations in bacteria harbouring them.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of resistant isolates to beta lactam and quinolone antibiotics is a great concern for the empirical treatment of nosocomial infections and public health because these traits can be horizontally-transmitted to other isolates by plasmids (18)(19)(20)(21). In the recent years, increase of ESBLproducing E. coli isolates has been reported from different parts of the world, particularly Asia (3).…”
Section: Discussionmentioning
confidence: 99%